Can product service systems support electric vehicle adoption?. (July 2020) - Ensslen, Axel; Gnann, Till; Jochem, Patrick; Plötz, Patrick; Dütschke, Elisabeth; Fichtner, Wolf
Graphical abstract: Highlights: Empirical insights on adoption of e-mobility product service systems are provided. The question whether product service systems can support EV adoption is analyzed. Research approach combines techno-economical evaluations with behavioral aspects. Organizations' additional willingness to pay for EV compensates their higher costs. Smart platform services could increase benefits of e-mobility product service systems. Abstract: Plug-in electric vehicles are seen as a promising option to reduce oil dependency, greenhouse gas emissions, particulate matter pollution, nitrogen oxide emissions and noise caused by individual road transportation. But how is it possible to foster diffusion of plug-in electric vehicles? Our research focuses on the question whether e-mobility product service systems (i.e. plug-in electric vehicles, interconnected charging infrastructure as well as charging platform and additional services) are supportive to plug-in electric vehicle adoption in professional environments. Our user oriented techno-economic analysis of costs and benefits is based on empirical data originating from 109 organizational fleets participating in a field trial in south-west Germany with in total 327 plug-in electric vehicles and 181 charging points. The results show that organizations indicate a high willingness to pay for e-mobility product service systems. Organizations encounter non-monetary benefits, which on average overcompensate the current higher total cost of ownership of plug-in electric vehicles compared to internal combustion engine vehicles. However, the willingness to pay for e-mobility charging infrastructure and services alone is currently not sufficient to cover corresponding actual costs. The paper relates the interconnected charging infrastructure solutions under study to the development of the internet of things and smarter cities and draws implications on this development.